2014
DOI: 10.1038/mi.2014.28
|View full text |Cite|
|
Sign up to set email alerts
|

Dendritic cells from aged subjects contribute to chronic airway inflammation by activating bronchial epithelial cells under steady state

Abstract: The mechanisms underlying the increased susceptibility of the elderly to respiratory infections are not well understood. The crosstalk between the dendritic cells (DCs) and epithelial cells is essential in maintaining tolerance as well as in generating immunity in the respiratory mucosa. DCs from aged subjects display an enhanced basal level of activation, which can affect the function of epithelial cells. Our results suggest that this is indeed the scenario as exposure of primary bronchial epithelial cells (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 50 publications
1
34
0
Order By: Relevance
“…Alterations in the functions of AECs at homeostasis may therefore modulate the response of DCs to infections. A previous study from our laboratory has demonstrated that inflammatory DCs from elderly individuals can modulate the function of AECs at homeostasis . Taken together, these studies suggest that interaction of AECs and DCs at homeostasis plays a major role in maintaining immunity and tolerance in the airways.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…Alterations in the functions of AECs at homeostasis may therefore modulate the response of DCs to infections. A previous study from our laboratory has demonstrated that inflammatory DCs from elderly individuals can modulate the function of AECs at homeostasis . Taken together, these studies suggest that interaction of AECs and DCs at homeostasis plays a major role in maintaining immunity and tolerance in the airways.…”
Section: Discussionsupporting
confidence: 62%
“…Mucus secretion was also observed by the cells. At this time these cells also displayed high level transepithelial electrical resistance (TEER) and resistance to dextran fluorescein isothiocyanate (FITC) migration measured as described earlier .…”
Section: Methodsmentioning
confidence: 54%
See 1 more Smart Citation
“…Recently, it has been proved that the dendritic cells (DCs) in the elderly have an activated phenotype and an increased secretion of pro-inflammatory cytokines, which are responsible for the infiltration of eosinophils, the airway remodeling and the increase of asthma and chronic respiratory diseases [ 47 ]. In the SLIT the oral DCs are the first structures involved in the mechanism, with the aim to modulate the allergen-specific antibody responses.…”
Section: Reviewmentioning
confidence: 99%
“…Viceversa , in the presence of injurious stimuli ( e.g., viruses and bacteria) elevated basal production of cytokines hampers release of pro-inflammatory mediators, as observed in aged and knockout animals [ 19 26 ]. Just recently, old dendritic cells (DCs) have been shown to contribute to chronic airway inflammation, releasing pro-inflammatory mediators, mostly tumor necrosis factor (TNF)-α, which affects primarily bronchial epithelial cell function in vitro, enhancing the epithelial barrier permeability, thus increasing susceptibility to infectious respiratory disease in ageing [ 27 ]. Finally, naïve CD4 + and CD8 + cells are reduced in aged animals and humans with an impaired conversion towards memory cells able to respond to new antigens in the context of respiratory tract [ 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%